(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Hazardous waste such as automotive paint sludge has a potential to be recovered or treated with advance method such as microwave assisted pyrolysis. It is an advantage for the process with the aid of microwave radiation to the system due to the high affinity of water in the automotive paint sludge which acts as the medium of heating in the microwave pyrolysis reaction. By having such process, not only it is good to dispose the automotive paint sludge but three different products have been recovered from that process such as solid char, liquid oil and gas. With the high hydrocarbon content in the automotive paint sludge, it was estimated that high valuable hydrocarbon might be recovered in the liquid product. From this research, three parameters were studied and analyzed for the product distribution and liquid oil recovered which are sample weight loading, microwave power level and radiation time. It was observed that best sample weight loading, microwave power level and radiation time to produce high liquid hydrocarbon oil were 200g, 1000W and 30 minutes respectively in which 0.1g or 0.27% was liquid oil recovered from overall sample weight loading.Â